Analysis and interpretation of inorganic mineral particles in "lung" tissues. - Gibbs, A. R. (1996)
Mineral analysis of tissue specimens has provided very useful information in pathological conditions associated with occupational exposures to mineral particles, particularly when combined with epidemiological information. Most of the data have been related to exposures to fibrous particles such as asbestos. More investigations of this nature are required in diseases associated with exposure to non-fibrous particles. In the future it is likely that these types of investigation will be extended into the effects of pollutants.